2017
DOI: 10.1186/s41610-016-0020-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation structure and human impact on understory honey plant richness: implications for pollinator visitation

Abstract: Background: Though the biomass of floral vegetation in understory plant communities in a forested ecosystem only accounts for less than 1% of the total biomass of a forest, they contain most of the floral resources of a forest. The diversity of understory honey plants determines visitation rate of pollinators such as honey bee (Apis mellifera) as they provide rich food resources. Since the flower visitation and foraging activity of pollinators lead to the provision of pollination service, it also means the enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, in our study, at the same site, the biomasses of undergrowth vegetation within poplar stands of different densities and clones were not significantly different, which is consistent with the observations of Zhang et al (2019) for the Pinus massoniana plantation. However, Cho et al (2017) reported that understory vegetation density was negatively correlated with canopy density. Additionally, shade was found to be the main factor affecting the growth and development of understory vegetation (Barbier et al 2008).…”
Section: R a F Tmentioning
confidence: 99%
“…However, in our study, at the same site, the biomasses of undergrowth vegetation within poplar stands of different densities and clones were not significantly different, which is consistent with the observations of Zhang et al (2019) for the Pinus massoniana plantation. However, Cho et al (2017) reported that understory vegetation density was negatively correlated with canopy density. Additionally, shade was found to be the main factor affecting the growth and development of understory vegetation (Barbier et al 2008).…”
Section: R a F Tmentioning
confidence: 99%
“…Vegetation structure is a useful surrogate for ecosystem attributes and ecological processes, e.g. microclimate (Milling et al ), carbon storage and sequestration (Wang et al ; Chazdon et al ), water yield (Filoso et al ), protection against soil erosion (Musick & Gillette ; Zhou et al ; Zhang et al ), improving water quality (Dosskey et al ), and pollination (Cho et al ). More broadly, if vegetation structure is on a trajectory to be restored to a target, it usually means restoration of composition and abundance of plant species (Liebsch et al ; Suganuma & Durigan ), microorganisms (Banning et al ), and faunal groups, such as soil fauna (Frouz et al ; Dalle Laste et al ), butterflies (Nyafwono et al ; Shuey et al ), amphibians (Díaz‐García et al ), reptiles (Kanowski et al ), and birds (Twedt et al ), will also be restored.…”
Section: Measuring Attributes Of Vegetation Structure As Indicators Omentioning
confidence: 99%
“…First, conversations with participating beekeepers indicated they prefer areas with some but not a lot of tree-cover as apiary sites. Second, a less dense canopy allows for more growth in the understory, including many shrubs and herbaceous species that provide a good source of pollen and/or nectar for honey bees (Lefrançois et al 2008;Latif and Blackburn 2010;Cho et al 2017). The urban class in the FEC was also further subclassified because it encapsulated a multitude of urban elements with varying potentials to host and support honey bee populations, including buildings, parking lots, parks and backyards.…”
Section: Lulc Rastermentioning
confidence: 99%
“…However, this neglects the understory of the forest, which, despite comprising less than 1% of the total biomass of forest ecosystems, accounts for upwards of 90% of the floristic diversity of the system, including many species that provide good forage for honey bees throughout the growing season, such as raspberry (Rubus idaeus), wild rose (Rosa acicularis) and aster (Aster sp.) (Gilliam 2007;Proctor et al 2012;Cho et al 2017). The presence of a forest understory is limited by the amount of light that reaches the forest floor, and therefore forests with less dense canopies will be more likely to support an understory with the rich floristic diversity conducive to supporting honey bee populations (Lefrançois et al 2008;Latif and Blackburn 2010;Cho et al 2017).…”
Section: Source Of Difference In the Modelsmentioning
confidence: 99%
See 1 more Smart Citation